The Beneficial Effect of Pollen on Varroa Infested Bees Depends on Its Influence on Behavioral Maturation Genes - Frizzera, Davide; Ray, Allyson M.; Seffin, Elisa; Zanni, Virginia; Annoscia, Desiderato; Grozinger, Christina M.; Nazzi, Francesco (Frontiers in Insect Science, 2022)
Honey bees collect nectar and pollen to fulfil their nutritional demands. In particular, pollen can influence longevity, the development of hypopharyngeal glands, and immune-competence of bees. Pollen can also mitigate the deleterious effects caused by the parasitic mite Varroa destructor and related deformed wing virus (DWV) infections. It has been shown that V. destructor accelerates the physiological and behavioural maturation of honey bees by influencing the interaction between two core physiological factors, Vitellogenin and juvenile hormone. In this study, we test the hypothesis that the beneficial effects of pollen on Varroa-infested bees are related to the hormonal control underpinning behavioural maturation. By analysing the expression of genes associated to behavioural maturation in pollen-fed mite-infested bees, we show that treatment with pollen increases the lifespan of mite-infested bees by reversing the faster maturation induced by the parasite at the gene expression level. As expected, from the different immune-competence of nurse and forager bees, the lifespan extension triggered by pollen is also correlated with a positive influence of antimicrobial peptide gene expression and DWV load, further reinforcing the beneficial effect of pollen. This study lay the groundwork for future analyses of the underlying evolutionary processes and applications to improve bee health.